HEALTH LOCUS OF CONTROL DENGAN KEPATUHAN MENJALANI DIET PADA PENDERITA DIABETES MELLITUS TIPE 2 - Dwitami, Meidiah; Eltrikanawati, T.; Pratiwi, Siska (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The majority of diabetes mellitus sufferers generally suffer from type 2 diabetes mellitus with around 90-95% of the total number of diabetes mellitus sufferers. The prevalence of diabetes mellitus has increased from year to year. Many people with diabetes mellitus have problems with adherence to diet. It is known that the level of compliance of patients with diabetes mellitus to carry out a diet is 65% but only 19% of patients comply with it. The purpose of this study was to determine the relationship of health locus of control to diet compliance in patients with type 2 diabetes mellitus in the working area of Sei Langkai Community Health Centre, Batam City. This type of research is quantitative with Cross Sectional approach method. This study used purposive sampling technique with a sample of 65 patients with type 2 diabetes mellitus in the working area of the Sei Langkai Health Centre, Batam City. The results showed that patients with type 2 diabetes mellitus in the working area of the Sei Langkai Health Centre, Batam City mostly had low health locus of control with 28 people (43.1%) not obedient to undergo a diet. The results of the chi-square test obtained a p-value of 0.000 <α 0.05. The conclusion of this study is that there is a relationship between health locus of control and diet compliance in patients with type 2 diabetes mellitus in the working area of the Sei Langkai Health Centre, Batam City.